SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KARYAWAN TERBAIK MENGGUNAKAN METODE TOPSIS PADA PT. PRIMITRA EXTRUSION - Juhriah, Een; Ramadhani, Rizky Nur (Universitas Majalengka, 2023)
The research objective is to design the Best Employee Selection Decision Support System Application using the Weighted Product Method at PT. Shuanghui Power Prima Based on Java. The method used to support decisions in research on selecting the best employees at PT Primitra Extrusion is to use the Topsis method. The results in the form of various problems related to the employee selection process encouraged the development of a method for selecting the company's best employees, in selecting employees at PT Primitra Extrusion using the Topsis method. The leadership uses criteria in selecting prospective employees, including discipline, communication, cooperation and initiative. So with this system, it makes it easier for leaders to select the best employees in the company accurately and effectively.